74.6k views
3 votes
Evaluate the function found in the previous step at X equals -3

Evaluate the function found in the previous step at X equals -3-example-1
Evaluate the function found in the previous step at X equals -3-example-1
Evaluate the function found in the previous step at X equals -3-example-2

1 Answer

5 votes

we know that

The equation found in the previous step is equal to


y=(5)/(3)x

For x=-3

substitute


\begin{gathered} y=(5)/(3)(-3) \\ \\ y=-5 \end{gathered}

therefore

f(-3)=-5

User Thom
by
6.3k points